Pengaruh Guru dalam Mengembangkan Kemampuan Berbicara Anak Usia Dini di PAUD - Mian Melli Jorika Br Sagala; Agnes Dewi Kartika; Neng Echa Ardila; Eri Rianti; Kartika Trihapsari; Dhea Ardiyanti; Hafiziani Putri; Asep Kurnia Jayadinata (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2026)
Speech skills in early childhood are the main foundation for children's language development. This study aims to analyze the influence of the role of teachers in developing early childhood speaking skills in An- Nahri Nurjanah Kindergarten. The focus of the research is directed at how teachers' strategies and iteration quality contribute to the enrichment of vocabulary and children's speaking fluency. The method used is a quantitative approach with a descriptive design. The data collection technique used was a likert scale questionnaire and children's speaking ability was measured using a performative test based on five indicators. Furthermore, data analysis techniques using SPSS include descriptive statistics and simple linear regression. The results showed that the role of teachers had a positive influence on the development of children's speech skills but was very small. Most of the development of a child's speaking ability is influenced by other factors such as the home environment, media stimulation, and the child's individual characteristics. This study emphasizes the importance of improving the quality of teacher-child interaction and the implementation of a more structured and consistent language stimulation strategy